2008
DOI: 10.3354/meps07410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fishing on population structure and life history of roman Chrysoblephus laticeps (Sparidae)

Abstract: The effects of fishing on the population structure and life history of roman Chrysoblephus laticeps, a protogynous hermaphroditic seabream from South Africa, were investigated by comparing fish from protected and exploited areas. Experimental (controlled) fishing and underwater visual census were used to sample roman and to measure population parameters inside and outside the Goukamma Marine Protected Area. Sites chosen for comparisons were adjacent and physically similar to reduce environmental influences on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 71 publications
4
33
0
Order By: Relevance
“…Sex allocation theory for sequential hermaphrodites (Warner 1975;Charnov 1982) predicts that size (age) at sex change should be reduced in populations where large adults have high mortality rates in order to compensate for potential impacts on breeding sex ratio. Previous studies have shown that several fish and invertebrate species (two temperate shrimp and one limpet) that are under harvesting pressure do indeed change sex at smaller sizes, supporting the theoretical prediction (Charnov 1981;Cowen 1990;Hannah and Jones 1991;Buxton 1993;Charnov and Hannah 2002;Platten et al 2002;Hawkins and Roberts 2004;Hamilton et al 2007;Götz et al 2008;Rivera-Ingraham et al 2011).…”
Section: Introductionsupporting
confidence: 66%
“…Sex allocation theory for sequential hermaphrodites (Warner 1975;Charnov 1982) predicts that size (age) at sex change should be reduced in populations where large adults have high mortality rates in order to compensate for potential impacts on breeding sex ratio. Previous studies have shown that several fish and invertebrate species (two temperate shrimp and one limpet) that are under harvesting pressure do indeed change sex at smaller sizes, supporting the theoretical prediction (Charnov 1981;Cowen 1990;Hannah and Jones 1991;Buxton 1993;Charnov and Hannah 2002;Platten et al 2002;Hawkins and Roberts 2004;Hamilton et al 2007;Götz et al 2008;Rivera-Ingraham et al 2011).…”
Section: Introductionsupporting
confidence: 66%
“…Parameter L 1 was used as an estimate of the average rate of somatic growth experienced between the ages of zero and one year. The percentile 95% confidence intervals (CI) were estimated for each rVBGF parameter using a bootstrapping procedure (Götz et al 2008).…”
Section: Growth Modelling and Estimation Of Initial Growth Ratementioning
confidence: 99%
“…A bootstrapping technique was used to estimate 95% CIs around each parameter (longevity and mean maximum size). Original sample means were bias-adjusted, and percentile CIs were calculated from the sorted bootstrapped estimates (Götz et al 2008). …”
Section: Longevity and Mean Maximum Sizementioning
confidence: 99%
“…In addition to altering sex ratios, fishing intensity can alter life history traits, such as length and age at maturity (Heino and Dieckmann, 2008;Sharpe and Hendry, 2009), the timing of sex transition in hermaphrodites (Hamilton et al, 2007;Götz et al, 2008), size and biomass spectra (Friedlander and DeMartini, 2002;Graham et al, 2005) and, in some cases, coral reef fish community structure through compensatory effects from decreased predation (Dulvy et al, 2004;Ruttenberg et al, 2011). The governments of Guam and Saipan have implemented marine protected areas as means to enhance fishery resources within and outside of those areas, and the CNMI has instituted a ban on spearfishing with scuba gear and has implemented restrictions on the use of gill, drag, and surround nets.…”
Section: Discussionmentioning
confidence: 99%